Le diaconat des femmes: Enquête sur les études vaticanes - Zagano, Phyllis (Proche-Orient chrétien, 2025)
This article traces the evolution of the debate on the ordination of women to the diaconate in the Catholic Church, from the initial discussions at the bishops' synod in the early 1970s to the recent statements by Pope Francis. It analyzes the various studies conducted by the International Theological Commission and the pontifical commissions, as well as the discussions during the global Synod on Synodality. The author presents the historical, liturgical, and theological arguments put forward for and against the restoration of the female diaconate, drawing on examples from the early Church and the evolution of practices up to the present day. The article highlights the complexity of the issue, the diversity of positions within the Church, and concludes with Pope Francis's negative response in May 2024, while emphasizing that the debate remains open. This summary reflects the main points addressed in the article and provides a clear understanding of its essence